Neutrophils in Leprosy - Schmitz, Veronica; Tavares, Isabella Forasteiro; Pignataro, Patricia; Machado, Alice de Miranda; Pacheco, Fabiana dos Santos; dos Santos, Jéssica Brandão; da Silva, Camila Oliveira; Sarno, Euzenir Nunes (Frontiers in Immunology, 2019)
Leprosy is an infectious disease caused by the intracellular bacillus Mycobacterium leprae that mainly affects the skin and peripheral nerves. One of the most intriguing aspects of leprosy is the diversity of its clinical forms. Paucibacillary patients are characterized as having less than five skin lesions and rare bacilli while the lesions in multibacillary patients are disseminated with voluminous bacilli. The chronic course of leprosy is often interrupted by acute episodes of an inflammatory immunological response classified as either reversal reaction or erythema nodosum leprosum (ENL). Although ENL is considered a neutrophilic-mediated condition, little is known about the direct role of neutrophils in ENL and leprosy disease overall. Recent studies have shown a renewed interest in neutrophilic biology. One of the most interesting recent discoveries was that the neutrophilic population is not homogeneous. Neutrophilic polarization leads to divergent phenotypes (e.g., a pro- and antitumor profile) that are dynamic subpopulations with distinct phenotypical and functional abilities. Moreover, there is emerging evidence indicating that neutrophils contribute to the inflammation triggered by M. leprae infection. In the present review, neutrophilic involvement in leprosy is discussed with a particular focus on erythema nodosum leprosum (ENL) and the potential of neutrophils as clinical biomarkers and therapeutic targets.